NOMINAL LEXEMES IN DERIVATIONAL REDUPLICATION OF MANDARIN - Shi Yuxin (Universitas Muhammadiyah Tapanuli Selatan, 2019)
Reduplication is a one of the creative ways in Mandarin. People usually reduplicate to express more deep lexical meaning or semantic meaning vividly. Reduplication is a process of forming new words by repeating an entire free morpheme (total reduplication) or part of it (partial reduplication). Morphologically, functions of Chinese reduplication may place categorically within the derivational domain of lexemes. In fact, whereas derivation typically forms new lexemes and can be category changing, reduplication often conveys values typically found in the inflectional domain. Using the M.D.S Simatupang context-free approach, this study clarifies various meanings of Chinese reduplication, then based on word membership tests and lexical decomposition tests as proposed by J.W.M Verhaar, this study analyzes derivational reduplication and inflectional reduplication in Mandarin. This research achieves shed new light on the reduplicative processes. As result, in nominal domain, reduplication gives as a result plural noun. In derivational domain, nominal lexeme in reduplication has flexible distribution of lexical items.